PENGARUH PENGETAHUAN, SIKAP DAN DUKUNGAN KELUARGA TERHADAP DIET HIPERTENSI DI DESA HULU KECAMATAN PANCUR BATU TAHUN 2016 - Lubis, Zulhaida; Tarigan, Almina Rospitaria; Syarifah, Syarifah (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Hypertension is a major risk factor causes of death. Hulu village is a village that has the highest number of hypertensive patients in Puskesmas Pancur Batu, Deli Serdang regency. Patients with hypertension in 2014, totaling 44, 2015, amounted to 56 people and in 2016 amounted to 108 people. This study aimed to analyze the influence of knowledge, attitude and family support for the implementation of hypertension diet in the village of Batu Pancur Hulu subdistrict. The study was cross-sectional study with explanatory approach. This study was conducted between April and June 2016. The population in the study were all patients with hypertension in the village of Batu Pancur Hulu subdistrict totaled 108 people and the entire population sampled. The data were obtained by questionnaire interviews, analyzed by multiple logistic regression at α = 0.05.The results showed that statistically the knowledge of (diet hypertension, food intake hypertension) and attitudes toward (diet hypertension, dietary diet hypertension) and family support include (support hope, real support, information support, emotional support) a significant effect on the implementation of the diet hypertension in the village of Hulu subdistrict Pancur Stone. Variables knowledge greater impact on the implementation of hypertension diet. Suggested to; (1) The District Government, Health Department and Community Health Center Pancur Batu District Deliserdang to work on improving counseling about diet hypertension, (2) Family in order to increase knowledge about the primary prevention of hypertension, so as to prevent this self-contained and provide motivation (support) to patients with hypertension in the implementation of hypertension diet.